Research of the current state and instruments of financial support for enterprises by the banking sector - Нєізвєстна, Олена Володимирівна (Technology audit and production reserves, 2016)
The aim of the paper is the identification and evaluation of the current state and the instruments of the financial support for enterprises from the side of the banking sector in the context of encouraging the banking system to increase and reduce the amounts of crediting for the real economy. By means of analyzing, systematizing and generalizing the scientific work of many scientists, the relationship between the results of activity of national enterprises and amounts of bank credits in the process of productive activities financing has been identified. During the research of the prospects to enhance bank crediting for the national enterprises the author has presented the position of an access of the Ukrainian enterprises to financial resources of banking institutions through the provision of the leadership in price setting, high quality of customer services, an offer of new products. It has been stressed that the elaboration of the mechanisms for long-term crediting in the banks of Ukraine should require the substantial development, as this will ensure the expanded reproduction of the production process, stability for the innovative enterprises development. It has been grounded the necessity for the implementation of a balanced policy by the National Bank of Ukraine, which should provide the orientation on promoting the investment activity in the country.